Fetal intestinal loop dilatation: Follow‐up and outcome of a series of 133 consecutive cases (the DILDIG study). (17th January 2023) - Mangione, Raphaële; Voirin‐Mathieu, Etienne; Yvert, Marianne; Fries, Nicolas; Mousty, Eve; Castaigne, Vanina; Muller, Françoise; Dreux, Sophie; ,
Abstract: Objectives: To define the prognostic markers of fetal dilated bowel loops. Methods: National non‐interventional study of 133 consecutive prenatal observations of dilated loops including ultrasound examinations, complementary laboratory tests, magnetic resonance imaging (MRI), outcomes, and postnatal diagnosis. Results: One hundred twenty seven cases were classified according to outcome: Group 1, very severe ( n = 43), Group 2, children needing specific care ( n = 39), and Group 3, healthy children ( n = 45). Prenatal ultrasound scan suggested duodenal obstruction in 30 cases, small bowel obstruction in 81, colonic obstruction in 11, and diffuse dilatation in 5. Diameter of dilated loops did not significantly differ between the groups. A poor prognosis was significantly associated with duodenal obstruction, genetic anomalies (53% vs. 21.8%), including aneuploidies or CFTR gene mutations and abnormal amniotic fluid biochemistry (86.4% vs. 38.7%). A good prognosis was associated with regression of dilatation and normal MRI. Conclusion: In this study, postnatal outcomes for fetuses with intestinal dilatation were best predicted by assessing the level of obstruction with prenatal ultrasound and MRI, determining the presence of associated malformations, amniotic fluid biochemical and genetic testing, and monitoring for regression of bowel dilatation. These results should help inform future guidelines on the prenatal and neonatal management of congenital intestinal obstruction. Key points: What is already known about this topic? The accurate diagnosis and prognosis of prenatally detected bowel loop dilatation are frequently difficult mainly due to the high frequency of associated anomalies that are difficult to specify prenatally. What does this study add? This work establishes the best prognostic markers in the case of prenatal dilated bowel loops, thus clarifying the guidelines for prenatal multidisciplinary centers and optimizing prenatal and neonatal management.